A Conceptual Framework Of Iranian Consumer Trust In Business To Customers Electronic Commerce - Meskaran, Fetemeh (2010)

(untitled)
Developing countries such as Iran are facing difficulties to establish e-commerce as part of their economics activities. Previous studies have shown that trust is one of the most important factors affecting the growth of e-commerce. The primary aim of this study is to develop a conceptual framework for Iranian customer trust in Business-to-Customer (B2C) e-commerce by identifying the antecedents and consequences of trust. A survey was conducted on Tehran customers in Iran through a set of questionnaires. Collected survey data are analyzed by using SPSS software based on 11 hypotheses. The proposed conceptual framework called ITM (Iran Trust Model), which is founded on the accepted hypotheses. In ITM model, two additional influencing factors are introduced and ineffective antecedents of trust are removed. The additional factors include the type of payment and reputation, which are two main antecedents of customer trust. The next factor is recommendation of friends as a type of reputation. A prototype of an online shopping website is implemented to validate the framework. The deployment of ITM in the shopping website has increased the rate of visitors to the website. An increase in the rate of visitors signals an increase in customer’s willingness to buy. This model concludes that improved trust affects on attitude and risk, and finally on willingness to buy.